Low-tie IMA and selective D3 lymph node sampling in laparoscopic rectal resection for carcinoma rectum: comparison of surgical and oncological outcomes with the open technique - Sindhu, Radha Sadasivan Nair; Natesh, Bonny; Rajan, Ramesh; Shanavas, Kakkat; Sukumaran, Geetha; Gayathri, Lekshmi Kumar (Journal of Gastrointestinal Oncology; Vol 8, No 5 (October 19, 2017): Journal of Gastrointestinal Oncology, 2017)
Background: Level of proximal lymphovascular ligation remains controversial in carcinoma rectum. High-tie inferior mesenteric artery (IMA) claims better lymph node clearance; low-tie IMA minimizes autonomic nerve injury (ANI) and ensures vascularity to anastomosis. Objective of this study is to compare postsurgical complications and oncological clearance in laparoscopic rectal resection (LRR) and open rectal resection (ORR) for carcinoma rectum, with low-tie IMA and selective D3 lymphadenectomy. Methods: Retrospective analysis was done comparing LRR and ORR done with low-tie IMA for carcinoma rectum/rectosigmoid for signi cant differences (P3 was similar in two groups. Histopathology characteristics were also comparable; including specimen length, lymph node yield, length of distal margin and pathologic TNM (pTNM) stage. Selective D3 lymphadenectomy was done in 37.5% LRR and 37.14% ORR. And 4.16% in LRR and 4.28% in ORR were had positive IMA root lymph nodes. Conclusions: The post-surgical complications and oncological clearance of LRR done with low-tie IMA and selective D3 lymphadenectomy were found equivalent to ORR. Low-tie IMA without routine splenic exure mobilisation had no technical issues regarding the anastomosis.